(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined from an ideal topological space into a bitopological space, called upper τ^(σ_1,σ_2)-continuous multifunctions and lower τ^(σ_1,σ_2)-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper τ^(σ_1,σ_2)-continuous multifunctions and lower τ^(σ_1,σ_2)-continuous multifunctions are investigated.